Salinity-water levels on productive performance, physiological and behavioral responses of 1/2 Dorper x 1/2 Santa Inês crossbred sheep - Matos Junior, Joab Leite; Furtado, Dermeval Araujo; Ribeiro, Neila Lidiany; Medeiros, Geovergue Rodrigues; Lopes Neto, José Pinheiro; Leite, Patricio Gomes; Rodrigues, Ladyanne Raia; Miranda, Jaciara Ribeiro (Semina: Ciências Agrárias, 2021)
The objective of this study was to evaluate the influence of four water salinity levels on productive performance, physiological and behavioral responses of confined sheep. Thus, 24 crossbred sheep, 1/2 Dorper x 1/2 Santa Inês were evaluated while receiving ration and water ad libitum. The experimental design was completely randomized, composed of four treatments (1.5; 3.0; 6.0 and 9.0 dSm -1) and six replicates. The water supply with salinity of up to 9.0 dSm -1 did not affect (P > 0.05) the physiological indexes, performance, or ingestive behavior of the animals, which were able to maintain normal physiological conditions even at times when the thermal comfort indexes were above the ideal. For voluntary water consumption, it was observed that there was a significant difference between treatments (P < 0.05), where animals consuming water with a conductivity of 1.5; 3.0 dSm -1 had lower consumption than those who received six dSm-1. The supply of water with a salinity of up to 9.0 dSm -1 did not affect the performance or the ingestive behavior of the animals, so waters with this salinity can be a valid alternative for crossbred sheep in the semi-arid region, as long as it is used seasonally and strategically.